(untitled) (Socious Journal, 2025)
The development of digital technology has changed people’s consumption patterns, encouraging a shift from conventional transactions to digital platforms. This phenomenon threatens the existence of traditional markets which are increasingly marginalized due to low adoption of digital technology, limited digital literacy, and minimal infrastructure and regulatory support. This study aims to analyze the understanding and utilization of digital marketing among traditional market traders, and to evaluate the role of the Student Creativity Program (PKM) as an intervention model in revitalizing the local economy. Using a descriptive quantitative approach, data was collected through a survey of traditional market traders. The results showed that WhatsApp Business (35%) was the most widely used digital platform, followed by Facebook Marketplace (22%) and Instagram (18%), while TikTok Shop was still low (10%). As many as 15% of traders have not used digital media at all. The level of digital literacy also varies, with 35% of traders in the "less" and "very less" categories. These findings underscore the urgency of ongoing training and mentoring through PKM, which has been proven to be effective in increasing digital promotion capabilities by up to 60%. Therefore, collaboration between the world of education, local government, and market communities is crucial to create traditional markets that are inclusive, adaptive, and highly competitive in the digital era.